Pengaruh Konsentrasi dan Lama Perendaman Ekstrak Air Daun Mimba (Azadirachta Indica) terhadap Hama Kepik Penghisap Buah Kakao (Helopeltis Spp) - Yovita Yasintha Bolly; Mario Malado (Fakultas Pertanian, Universitas Nusa Nipa, 2025)
The study entitled The Effect of Concentration and Soaking Duration of Neem Leaf Water Extract (Azadirachta indica) on Cocoa Pod-Sucking Bug Pests (Helopeltis spp.) was conducted at the Field Laboratory (LL) of the Department of Agriculture and Plantation of East Nusa Tenggara Province, located at RT 003, RW 009, Kota Uneng Village, Alok District, Sikka Regency, from April 2016 to June 2016. The objectives of this study were: (1) to examine the effect of the concentration of neem leaf water extract (Azadirachta indica) in controlling cocoa pod-sucking bugs (Helopeltis spp.); (2) to examine the effect of the soaking duration of neem leaf water extract (Azadirachta indica) in controlling cocoa pod-sucking bugs (Helopeltis spp.); and (3) to determine the combined effect of concentration and soaking duration of neem leaf water extract (Azadirachta indica) in controlling cocoa pod-sucking bugs (Helopeltis spp.). This study was a two-factor experiment, namely concentration and soaking duration, arranged using a Completely Randomized Design (CRD) with three replications, resulting in seventy-two (72) experimental units. Factor I: Concentration factor consisted of four (4) levels, namely: K0 = Control (without neem material/sterile water), K1 = Concentration of 1,000 ppm = 0.1%, K2 = Concentration of 2,500 ppm = 0.25%, and K3 = Concentration of 5,000 ppm = 0.5%. Factor II: Soaking duration factor consisted of six (6) levels, namely: L0 = Control (without neem material/sterile water), L1 = Soaking duration of 1 day, L2 = Soaking duration of 2 days, L3 = Soaking duration of 3 days, L4 = Soaking duration of 4 days, and L5 = Soaking duration of 5 days. The results showed that on the first day of observation, the lowest and highest average numbers of punctures were 62.25 and 104.25 punctures (control), 44.33 and 71.86 punctures (1,000 ppm treatment), 38.75 and 77.14 punctures (2,500 ppm treatment), and 32.14 and 65.17 punctures (5,000 ppm treatment), respectively. Based on these data, it was observed that there were differences in the number of Helopeltis punctures on cocoa pods due to the application of neem leaf pesticide on the first day. The application of neem leaf pesticide was able to reduce the number of Helopeltis punctures on cocoa pods. This effect continued until the 10th day of observation, where the average number of punctures decreased progressively (and even reached zero) as the concentration and soaking duration of neem leaves increased. By the 10th day, there were still 132 Helopeltis punctures on cocoa pods in the control treatment, while the number of punctures in the other treatments continued to decrease, with some treatments showing no punctures at all.